Industrial training report: Nasi Kandar Hussain. Special project: Financial performance of restaurant Nasi Kandar Hussain Pekan Baru Sungai Petani / Shahirah Zainol Abidin - Abidin, Shahirah Zainol (Universiti Teknologi MARA, Perlis, 2021)
My memorable and enlightening 6-month industrial training began here at Hasani Group Sdn Bhd. My industrial training began on February 2021 and will end on July 23 2021. Puan Renuga as my supervisor at Hasani Group ha been helping me since day one of internship until the end of internship. She has been a great help for me in completing my internship at Hasani Group in Account Department. And Manager of Hasani Group, En Anwar gave me a lot of experience in getting know my scope of job and have been guiding me in completing my task during my internship. I have been assigned to two department of business which account department of Hasani Bookshop and Account Department of Restaurant Hussain Nasi Kandar and Fatimah Bakey. In Account Department of Hasani Bookshop, I have been given responsible to manage the Credit Purchase, Credit Note, Good Return Advice and Good Return Note from the supplier and clients. I have also been assigned to do filling for credit payment filling for salary. In Account Department of Restauran Nasi Kandar Hussain and Fatimah Bakery, I have been assigned to print payment voucher, did cashbook, key in the data sales and expenses in Mr Accounting system and doing filling for credit payment of Restaurant and Bakary. I have also learn and did time management for salary for local workers. I also has learned to key in Salary and learned to calculate the EPF, SOCSO and SIP for local workers. In this report, the discussion is about the financial performance of Restaurant Hussain Nasi Kandar Hussain Pekan Baru SP during the Pandemic Covid-19. This research using Industry and Company analysis to analyse the financial performance of the restaurant. The Financial Ratio that will be using to analyse financial performance are Liquidity Ratio, Profitability Ratio and Efficiency Ratio